Velocity-Adaptive Prescribed Performance Control for Carrier-Based Aircraft Based on Guardian Maps - Chenliang Li; Jizhou Lai; Boyi Chen; Yanbin Liu (International Journal of Aerospace Engineering)
The automatic carrier landing process is a significant and complex due to the plant variation of carrier-based aircraft. To reasonably identify the stability interval for specific performance, an adaptive control strategy based on the guardian map approach is proposed. Prescribed performance, namely, stability margin, damping requirements, or flying quality requirements, is analytically formulated using a guardian map. The null space of guardian maps restricts the prescribed performance regarding the poles’ location. The feasible corridor of control parameters is generated based on the null space of guardian maps. Besides, a velocity-adaptive prescribed performance control method is proposed to conduct the attitude control of carrier-based aircraft. Simulation shows that the short-period mode of carrier-based aircraft will be driven from unstable to stable as the velocity decreases. Moreover, simulation results demonstrate the proposed control method and indicate that the attitude loop control of carrier-based aircraft possesses more underdamped responses as the velocity decreases.